2016
DOI: 10.2169/internalmedicine.55.6293
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Hospital Volume on the Performance of Residents on the General Medicine In-Training Examination: A Multicenter Study in Japan

Abstract: Objective Although several studies have been conducted worldwide on factors that might improve residents' knowledge, the relationship between the hospital volume and the internal medicine residents' knowledge has not been fully understood. We conducted a cross-sectional study to compare the relationships of the hospital volume and hospital resources with the residents' knowledge assessed by the In-training Examination. Methods We conducted a retrospective survey and a clinical knowledge evaluation of postgradu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…The Japan Organization of Advancing Medical Education Program (JAMEP), a non-profit organization, has been implementing the GM-ITE since 2011 as an objective evaluation of the basic clinical competency of junior resident physicians (postgraduate years PGY-1 and PGY-2) [5][6][7][8][9]. The GM-ITE is a multiple-choice knowledge test.…”
Section: Gm-itementioning
confidence: 99%
“…The Japan Organization of Advancing Medical Education Program (JAMEP), a non-profit organization, has been implementing the GM-ITE since 2011 as an objective evaluation of the basic clinical competency of junior resident physicians (postgraduate years PGY-1 and PGY-2) [5][6][7][8][9]. The GM-ITE is a multiple-choice knowledge test.…”
Section: Gm-itementioning
confidence: 99%
“…Data from the 2013 GM‐ITE showed that appropriate emergency department (ED) workload, inpatient caseload, and online learning resource were associated with greater clinical knowledge 2. In addition, in 2014, we found that factors affecting hospital volume, including the number of hospitalizations, had a positive impact on GM‐ITE scores 3. While our team have been extensively studied factors related to the performance of the GM‐ITE, because previous studies were analyzing cross‐sectional data, we could not evaluate the improvement in GM‐ITE score over time.…”
Section: Tablementioning
confidence: 82%
“…2 In addition, in 2014, we found that factors affecting hospital volume, including the number of hospitalizations, had a positive impact on GM-ITE scores. 3 While our team have been extensively studied factors related to the performance of the GM-ITE, because previous studies were analyzing cross-sectional data, we could not evaluate the improvement in GM-ITE score over time. In this context, we investigate how educational environment of hospitals is related to the improvement in GM-ITE score using the longitudinal data obtained during two consecutive years.…”
mentioning
confidence: 97%
“…In 2016, Mizuno et al 17 reported the performance of 2015 junior resident physicians (postgraduate years 1 and 2) working in 208 Japanese hospitals nationwide in the General Medicine In‐Training Examination (GM‐ITE). GM‐ITE scores were generally higher for residents working at training sites with a greater volume of patient admissions and a lower number of nonresident physicians.…”
Section: Discussionmentioning
confidence: 99%